Overview of Light Decay Due to Environmental Effects for Light Emitting Diode - Raul, Debashis; Bhattacharya, Payel; Ghosh, Kamalika (International Journal of Computer Sciences and Engineering, 2025)
Now a day’s LEDS have also been used in outdoor illumination due to their low power consumption and high life as compared with conventional lighting solutions. These LEDs may be operated in an environment with high humidity and high temperature. All these environmental effects may lead to increase the light decay and end of the result leads to lamps failure. In this paper, Surface Mounted (SMD) and Chip on board (COB) type LEDs were studied by high humidity and high temperature in the environment test chamber to find their light decaying behavior. Another aging test would be established by using rapid life cycle switching mechanisms. It is found that environmental effects as well as rapid switching are the serious causes for lumen decay of these LEDs.